Modified Cascaded H-bridge Multilevel Inverter for Hybrid Renewable Energy Applications. Issue 6 (2nd November 2022) - Sandhu, Mamatha; Thakur, Tilak
Abstract : Renewable energy sources and technologies have the potential to provide solutions to the long-standing energy problems being faced by developing countries. The renewable energy sources like wind energy, solar energy, geothermal energy, ocean energy, biomass energy and fuel cell technology can be used to overcome energy shortage in India. This paper proposes a modified multi-level inverter (MLI) topology for Hybrid Renewable Energy Sources (HRES) and a design of hybrid solar-wind power generation model with 9-level, 13-level and 17-level inverter topologies. A HRES connected to a modified Cascaded H-Bridge Multi Level Inverter (CHB-MLI) is developed, whose switches are controlled using Artificial Neural Network (ANN) model. The proposed hybrid energy system model consists of 10 Metal Oxide Semiconductor Field Effect Transistors (MOSFETs) that intend to give 17 levels of output voltage. The proposed topology performs effectively with reduced number of components and reduced Total Harmonic Distortion (THD). The performance of the proposed system is analyzed by designing the model in MATLAB/SIMULINK environment. The simulation results of the proposed inverter for the HRES application are compared with the results of the existing topologies to show the effectiveness of the proposed model.